THE RELATIONSHIP BETWEEN TEACHERS’ MASTERY EXPERIENCE AND TEACHER SELF-EFFICACY: A META-REGRESSION OF CROSS-SECTIONAL STUDIES - Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari; Ibrahim, Mohd Burhan; Othman, Joharry (2017)
Purpose -The objective of the meta-analysis was first to substantiate the magnitude of the effect size (ES) of the relationship between mastery experience and teacher self-efficacy. Second, the meta-analysis was also aimed to search for the research characteristics that moderate the mastery experience-teacher efficacy relationship. Methodology - A total of 26 original studies, involving 10,752 teachers was included in the meta-analysis. To identify the moderators, the study applied meta-regression procedure. Findings - The results supported the expectation that mastery experience positively influences teacher self-efficacy. Collectively sample charactistic, self-efficacy measure and work culture impacted the variability of the effects size.